Autologous platelet concentrates and their applicability in Dentistry (Research, Society and Development, 2022)
The development of technologies based on platelet concentrate obtained through centrifugation and manipulation methods from a blood sample aims to optimize tissue healing and promote tissue regeneration. Objective: to address considerations about autologous platelet concentrates and their applicability in Dentistry. Methodology: a retrospective analysis of the literature from 2001 to 2022 was carried out, focusing on the evolution and use of autologous blood concentrates. The following search terms were used: platelet-rich plasma, fibrin-rich plasma, autologous hemoconcentrates, tissue regeneration and healing. The literature search was carried out through a search in PubMed, Google Scholar, SciELO and BVL databases. Bibliographic Review: Platelet-rich plasma (PRP) was the first generation of derivatives from human blood samples, used for this purpose. Depending on the technique for preparing platelet concentrates, they are divided into four categories according to their leukocyte and fibrin content. Conclusion: Platelet aggregates can induce the activation of fibroblasts and the formation of collagen deposits, in addition to platelets and growth factors used in tissue repair. Thus, they optimize the results of treatments in dentistry, such as skin filling, treatment of acne scars, dental implants and dentoalveolar surgeries.